Generating French virtual commuting networks at the municipality level - Maxime Lenormand; Sylvie Huet; Floriana Gargiulo (Journal of Transport and Land Use)
We aim to generate virtual commuting networks in the rural regions of France in order to study the dynamics of their municipalities. Since it will be necessary to model small commuting flows between municipalities with a few hundred or thousand inhabitants, we have opted for the stochastic model presented by Gargiulo et al. (2012). This model reproduces various possible complete networks using an iterative process, stochastically selecting a workplace in the region for each commuter living in the municipality of a region. The choice is made considering the job offers in each municipality of the region and the distance to all of the possible destinations. This paper will present methods for adapting and implementing this model to generate commuting networks between municipalities for regions in France. We address three different issues: How can we generate a reliable virtual commuting network for a region that is highly dependent on other regions for the satisfaction of its residents’ demands for employment? What about a convenient deterrence function? How can we calibrate the model when detailed data is not available? Our solution proposes an extended job search geographical base for commuters living in the municipalities; we compare two different deterrence functions and we show that the parameter is a constant for network linking municipalities in France.